The The Effect of Differentiated Learning on Creativity and Independent Learning of Class VIII Students in Bintan District - Lia Nur'aliah; Tian Belawati; C. Rudy Prihantoro (Universitas Cokroaminoto Palopo, 2025)
This research aims to determine the effect of differentiated learning on the creativity and learning independence of class VIII students in Bintan Regency. This research uses a quantitative method with a quasi-experimental design with a nonequivalent pretest and posttest control group design. The sample for this research was class VIII students of SMPN 2 Bintan as a sample of Driving Schools and SMPN 6 Bintan as a sample of Independent Curriculum Implementation Schools who were chosen randomly. Data was collected through creativity and learning independence questionnaires which were filled out by students before and after differentiated learning was implemented. Data were analyzed using the Manova parametric test if the data was normally distributed and the Mann-Whitney non-parametric test if the data was not normally distributed. Both tests were used to determine whether there were significant differences in the combination of dependent variables based on the nominal independent variable category. The research results showed that students' creativity and learning independence experienced significant differences after the implementation of differentiated learning, with a significance value of Asymp. (sig.) 0.000 in the experimental class. There was the highest increase in the indicator of fluent thinking of 7.4% in student creativity and the indicator